PELESTARIAN SUBAK DALAM UPAYA PEMBERDAYAAN KEARIFAN LOKAL MENUJU KETAHANAN PANGAN DAN HAYATI - Martiningsih, Ni Gst.Ag.Gde Eka (Bumi Lestari; Vol 12 No 2 (2012), 2012)
This paper  present in accordance with the field research findings (empirical data), observation conducted by the writer. This research  is a case study  in   Subak Wangaya Betan (SWB) focus on preserving  Subak through revitalizing  local knowledge .  Now a days it is very rare researches  focus on local knowledge  roles in Subak, how ever  in fact its very important to empower local knowledge in strong cultural community. SWB is one of successful subak in Bali on preserving local knowledge to be a core rule on sustainable agriculture. Many debates on issue that Bali only focus on tourism industry will be refused when SWB will nominate by UNESCO being one of natural cultural heritage of Bali province. The focus of this research is to observe how SWB still exist and developed preserving their activities on agriculture areas and how strugling of SWB face of many dispute of environment and natural  disaster.  The findings of this research are the involvement of  local knowledge activities and  ritual  on somehow  was ignorance, but in fact its very tough to consolidate community to encourage their awreness of environment problem. In order to get food security and biosecurity interest, the research need to more deeper observe the implementation of the rituals activities and local knowledge roles in the reality of farmer life.
Keywords: local knowlege, subak, food security, biosecurity, role